Belajar dari Kepemimpinan Saul: Membangun Fondasi Kepemimpinan Kristen yang Kokoh - Grecetinovitria Marliana Butar-butar; Putri Yulia Citra Br. Berutu; Juliana Hutabarat (LPPM - STT Kadesi Bogor, 2024)
Leadership has been an integral part of human life since ancient times. This article examines lessons from Saul's leadership in a Christian context, focusing on Biblical principles such as obedience, humility, and openness to the input of others. In this article the author uses a research method using a qualitative descriptive approach with literature analysis. So that we can describe learning from Saul's Leadership: Building a Solid Christian Leadership Foundation. The discussion includes the concept of leadership charisma, Saul's charisma and courage, as well as Saul's mistakes in disobedience and arrogance. The conclusion emphasizes that charisma and courage must be balanced with obedience and humility to build a solid foundation of Christian leadership.